Electronic transition dipole moment: a semi-biorthogonal approach within valence universal coupled cluster framework - Bhattacharya, Debarati; Vaval, Nayana; Pal, Sourav (International Journal of Quantum Chemistry, 2014)
Electronic dipole strengths (square of transition moments) and oscillator strengths are evaluated for various transitions, arising from the ground state to a few valence excited states. Parallel to two other methods of calculating the dipole strength within the Fock-space multireference coupled cluster framework, a new semi-biorthogonal approach is formulated and implemented in this article. This semi-biorthogonal approach can evaluate dipole strengths at a lower computational effort than the biorthogonal approach without compromising on the accuracy. This new method is compared and tested against the previously developed expectation value and biorthogonal approach for various molecular transitions. (C) 2014 Wiley Periodicals, Inc.
Keywords: electronic transition dipole; Fock-space; oscillator strength; semi-biorthogonal expectation value